Hotpoint Monitoring System Power Cable Termination Based On Internet of Things (IoT) Using Telegram Bot - Muhammad Syahri; Agus Urip Ari Wibowo; Dadang Syarif Sihabudin Sahid (International ABEC, 2022)
Electricity is energy that is needed in any field, both industry and ordinary people. To be able to produce good quality electrical energy, it is necessary to monitor and maintain electrical power equipment to prevent equipment damage that can interfere with the electrical energy distribution system to consumers. One of the disturbances that are often experienced is the Hotpoint at the terminal connection section between the conductor cable and the equipment at the substation. Hotpoint is an increase in the production of acoustic pulses (sound) and an increase in temperature that causes energy dissipation resulting in the heating of a localized area. This Hotpoint will cause damage to the equipment if it occurs for a long time. In this research, a Hotpoint monitoring system for 20 kV power cable termination based on the Internet of Things was built to monitor the temperature condition of the 20 kV power cable termination in real-time. This system uses the MLX90640 IR Thermal Camera sensor as the cable termination temperature gauge and the DHT22 temperature sensor to measure the 20 kV cubicle panel temperature. This temperature value will be compared to determine whether there is a Hotpoint at the termination of the 20 kV power cable. This system uses a MySQL database and HTTP protocol for communication between the Raspberry Pi4 and the website dashboard, then for notifications using the Telegram bot. The sensor accuracy test is carried out by comparing the temperature value between the DHT22 sensor and the Hygrometer with an average measurement value difference of -1.7%, while the MLX90640 and Fluke Ir 568 sensor accuracy tests have an average measurement value difference of -1.13%°C. Based on the sensor accuracy testing, it can be concluded that all sensors have a fairly good performance in measuring the required temperature parameters.